A positioning correction method for turbine blade film cooling holes. Issue 1 (1st November 2022) - Li, Pengfei; Guo, Jianmei; Cai, Yanhua; Wu, Dongbo; Liang, Jiawei; Wang, Hui; Han, Xiao
Abstract: It is significant to improve the machining accuracy of film cooling holes on aero-engine turbine blades. This paper presents a method to correct the position of film cooling holes on turbine blades. In this method, the pre-positioning algorithm and the precise positioning algorithm are proposed. The pre-positioning algorithm introduces the blade structure information. In the precise positioning algorithm, 3D coordinate transformation, ∠B and ∠C of 5-axis machine tool updating, iteration points creating based on the normal vector are designed. The operation of the gas film cooling hole correcting by the method is given. Experiment shows that, after 7 iterations, the error is reduced to 0.0344mm, achieving high-precision positioning of turbine blades. Furthermore, the coordinates are corrected to realize the high-precision machining of the film cooling holes, which can improve the cooling performance of turbine blades.